THE NATURALNESS IN THE TRANSLATION OF GUARDIANS OF GA’HOOLE: THE CAPTURE NOVEL BY KATHRYN LASKY - Permatasari, Idha Dwi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
A research about translation is highly observed because people nowadays are interested in the meaning of the foreign language. In this research, the researcher wants to find out naturalness form in the translation and how much the translation sounds natural to the target reader. The researcher uses English and Indonesian version of Guardians of Ga’Hoole: The Capture novel by Kathryn Lasky to obtain the data. The researcher limits the data into the first 3 chapters of the novel. The method that the researcher uses to analyze the data is a qualitative descriptive method which covers the analysis of the source text and the target text. The researcher hopes this research can be useful for people who study translation, especially in the field of naturalness and people who conduct research about naturalness as their additional reference. There are 20 data of naturalness found in the novel and the most data found are sentences amounted to 13 data, then phrase amounted to 4, word 2 data, and the last is clause 1 data. The quality of the naturalness found in the novel is highly natural, 11 data of highly natural and 9 of natural.